A narrative based exercise to introduce clinical training to medical students: a pilot study - Amarasuriya, M.Y.; Wijewickrama, P.S.A.; Kularathne, S.S.L; Wickramasinghe, D.S.A.; Nanayakkara, K.D.L.; Jayasinghe, K.S.A. (My University, 2012)
A narrative based approach was adopted in an activity conducted as part of a five day orientation programme for medical students in the third academic year, who were starting clinical rotations. Groups of students were allocated to patients to elicit their life stories, in the form of a narrative, similar to a biography.